Industrial growth models by input-output analysis and an institutional approach to the automotive industry in China and Turkey - Unal, Emre (Springer Heidelberg, 2021)
This work introduces a hypothetical extraction method (HEM) using weighted multipliers approach through input-output analysis, in combination with an institutional approach, to assess productivity growth in industries in both the domestic consumption goods and export goods sectors. It aims to concretely define what creates industrial growth models and to discover why some industries are less competitive than others and end up with trade deficits. For the research, China and Turkey were compared with each other. This research reveals that the transport equipment industry while China's growth was consumption-led, Turkey's was export growth. Both countries experienced trade deficits in the transport equipment industry, which is related to the automotive industry. The main differences in the industrial growth models of the two countries are assessed by looking at institutional factors.
Keywords: Automotive industry; Hypothetical extraction method; Industrial growth model; Input-output analysis; Institutional approach